MEMBANGUN KEWIRAUSAIIAAN DALAM PERSPEKTIF AGRIBISNIS DI ERA GLOBALISASI - Fatima, Imaculata (AGRICA, 2008)
To face the economic problems in this global era, the agriculture sector can support the needs of many people in Indonesia, particularly those who have a low economic background. Recently most farmers have worked hard to increase their productivity. However, they often find have problems or handicaps such as (1) human resource is still low; (2) financial problems; (3) land is not enough to produce commodities; (4) infrastructures are not available enough; (5) appropriate technologies are not enough; (6) networking system of agriculture is not established yet to all agriculture sector; (7) most of the farmers are depending on the natural support; (8) skill, spirit entrepreneurship and sense of self-support of the farmers are not optimized. Regarding these problems, in fact, most farmers are developing their agriculture sectors without considering the quality of their products which is very important to the consumers, the second problem is economic global which is running fast. This can cause problems for farmers. It is therefore, all the farmers should be motivated to improve their capability on agriculture and their feeling confidence. Based on the issues, this article focuses on the single problem like "is it relevant to give understanding about the business which oriented to agribusiness toward the global area. It is summed up that in global marketing, the agriculture sector is relevant to wake the spirit, entrepreneurship ability of the farmers and oriented to agribusiness. Then they should consider the efficiency, competitive, productivity, viable, marketing strategic and self-support in order to place themselves well either in the local, regional or national level, even at the international level.